Proyeksi Daerah Potensi Banjir Tahun 2031-2040 Berdasarkan Skenario Iklim Representative Concentration Pathways 4.5 - Presli Panusunan Simanjuntak; Dian Paolo (UNIVERSITAS NEGERI MAKASSAR, 2022)
AbstractClimate change has many impacts. One of them is the possibility of increased flood potential areas. This study aims to determine the results of future rainfall projections related to potential flooding in Bojonegoro District, East Java Province based on Representative Consentration Pathways (RCP) 4.5. The data used are rainfall of the demographic period 1991-2010. Data projection processing uses the Pathways Concentration (RCP4.5) Representative scenario model for rainfall with the netCDF (.nc) format of the GCM CORDEX model (Model for Climate Interdisciplinary Research) with a resolution of up to 10 x 10 km in the period 2006-2040 These data are divided into 2006-2015 for data correction and 2031-2040 data. This study uses several parameters to create a potential flood map such as flow density, land cover, slope and soil texture. These parameters are combined using a weighted overlay technique to produce a potential flood distribution. The results showed that in the 1991-2010 period the level of flood hazard in Bojonegoro Regency was in the safe category of 2,056 ha, the low category was 51,026 ha, the medium category was 82,879 ha and the high category was 95,392 ha. Compared to the hazard map, the high flood potential category in the 2031-2040 increased the area increase by 4.626 ha (2.0%). AbstrakPerubahan iklim mempunyai dampak yang cukup luas. Salah satunya adalah meningkatkan potensi banjir. Penelitian ini bertujuan untuk mengetahui hasil proyeksi curah hujan di masa mendatang yang berkaitan dengan potensi banjir di Kabupaten Bojonegoro, Jawa Timur berdasarkan skenario Representative Consentration Pathways (RCP) 4.5. Data yang digunakan adalah curah hujan observasi wilayah Kabupaten Bojonegoro periode 1991-2010. Data proyeksi yang digunakan adalah RCP 4.5 dengan format netCDF (.nc) dari model CORDEX dengan resolusi 10 km x10 km periode 2006-2040. Data tersebut dibagi menjadi 2 yaitu 2006-2015 untuk mengkoreksi data model dan data proyeksi 2031-2040. Penelitian ini juga menggunakan beberapa data untuk membuat peta rawan banjir yaitu data kerapatan aliran, tutupan lahan, kemiringan lereng dan tekstur tanah. Parameter-parameter tersebut digabungkan menggunakan teknik overlay berbobot untuk menghasilkan sebaran potensi banjir. Hasil penelitian menunjukan pada periode 1991-2010 tingkat kerawanan banjir Kabupaten Bojonegoro kategori aman seluas 2.056 ha, kategori rendah seluas 51.026 ha, kategori sedang seluas 82.879 ha dan kategori tinggi seluas 95.392 ha. Dibandingkan dengan peta rawan, maka potensi banjir kategori tinggi pada periode proyeksi 2031-2040 mengalami peningkatan luas sebesar 4.626 ha (2.0%).